POST-STROKE ELDERLY POSITIVE DEVIANCE IN BANDAR SETIA VILLAGE, PERCUT SEI TUAN DISTRICT, PERCUT SEI TUAN DISTRICT IN 2023 - Lidya Natalia Br Sinuhaji; Ida Yustina; Nurmaini Nurmaini; R Kintoko Rochadi; Fikarwin Zuska; Fazidah Fazidah (International Journal of Midwifery Research, 2023)
Elderly is a human age group that is susceptible to disease and even has a high risk of paralysis. One of the diseases that are often experienced by the elderly is stroke. Post-stroke sufferers often experience depression caused by inability to work due to disabilities and lack of social activities, so that stroke sufferers depend on emotional and physical support from their families. Stroke is a disease that is a problem in the world, the world stroke organization notes that 85% of people have a stroke risk. In Asian countries, one of which is Indonesia, it is estimated that 500 thousand people have a stroke every year. According to the incident figures, around 2.5% died, and the rest experienced mild to severe disabilities. Stroke is the number 1 cause of serious disability and persists in the world. In Indonesia, the problem of stroke is important because the incidence rate is highest in Asian countries. The type of research used by researchers was qualitative research with a descriptive approach. This type of research was chosen because the researcher wanted to see or explore a deep understanding and meaning of what happened to individuals or groups in this context, namely the elderly who had a stroke. In this study there are four data conclusions that will be discussed by researchers. The conclusions of the four data are: (1) The physical condition of the elderly after a stroke, (2) The psychological condition of the elderly after a stroke, (3) The social condition of the elderly after a stroke, (4) The environmental condition of the elderly after a stroke.